Towards Universal Screening for Colon Cancer: A Cheap, Reliable, Noninvasive Test Using Gene Expression Analysis of Rectal Swabs. (29th January 2012) - Smith, Andrew P.; Chiu, Yanek S. Y.; Lee, Nancy M.
Abstract : Though colon cancer is the second leading cause of cancer deaths in the US, it is entirely preventable through early screening to detect and remove adenomatous polyps. Colonoscopy has long been regarded as the "gold standard" but is expensive, invasive, and uncomfortable, and only about half those considered at risk for colon cancer currently submit to colonoscopy or to less reliable alternatives such as fecal occult blood test. Here we describe the use of gene expression analysis to detect altered expression of certain genes associated with not only colon cancer but also polyps. The analysis can be performed on rectal swabs, with specimens provided in a routine doctor's office visit. The existence of this cheap and simple test, together with an active program to encourage individuals to submit to screening, could help eradicate colon cancer.